Procedimentos e análises da orçamentação de um modelo BIM em dois níveis de desenvolvimento de objetos - Gabriel Victoria Tassara (2019)
This research presents Building Information Modeling (BIM) procedures to associate technologies and processes in two stages, the modeling and budgeting of a commercial building project. The area of this work is directed towards the execution of cost estimation of a model in different stages of the project through the Vico Office platform. The main objective of this study is to develop a process that links BIM 3D and BIM 5D, maximizing the advantages of this system in budgeting construction projects. This was achieved through the union of two academic researches and also allowed a comparison between the costs measured in BIM and without the aid of this system. The research method adopted was Design Science Research, which fit the work in order to understand and improve the techniques of BIM 5D, linking them to the modeling steps. A process flow was built that integrated modeling and model budgeting into different design stages and with objects at different development levels. The main results obtained were the exposure and validation of this flow that, besides the link between the steps, allowed the efficiency evaluation through five indexes: Accuracy, Agility, Automation, Integration and Interoperability. Within this process stand out the interoperability between platforms through a plug-in, automatic budget extraction through simulations of design changes and the 5-minute difference in time spent budgeting the model with objects at different levels. of development. The budgeting result in BIM showed a difference of approximately 5% compared to the one previously executed without the use of this system. By comparing the results between models at different levels of development, a difference of approximately 3,3% was measured.